PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP PENGELOLAAN SKALA PRIORITAS DANA DESA DI DESA RENGGING PECANGAAN JEPARA - Joko Lelono; Aris Suliyono (Judge : Jurnal Hukum, 2026)
This research aims to determine the influence of the quality of human resources (HR) on the management of Village Fund priority scales in Rengging Village, Pecangaan, Jepara. Village Funds as a village development instrument require competent village officials so that their management is effective, transparent and accountable. The research uses an empirical juridical approach with descriptive qualitative methods through interviews and document studies. The research results show that the quality of human resources has a significant effect on the planning, implementation and accountability of Village Funds. The main obstacles found were limited technical competence and a lack of ongoing training for village officials. Therefore, increasing HR capacity is the key to realizing Village Fund management that is right on target and in accordance with statutory provisions.